Analisis Profesionalisme Kerja pada Sekretaris di Perusahaan Bulog - Dilan Arya Saputra; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Kajian Administrasi Publik dan ilmu Komunikasi, 2024)
This research analyzes the professionalism of secretaries in PT Bulog by examining their attitudes, skills, and competencies in fulfilling their roles. It explores how corporate culture influences secretarial professionalism, strategies for addressing workplace challenges, and the impact of ethical practices and personal values on work quality. Data was collected qualitatively through interviews, observations, and documentation. Results reveal that professionalism encompasses effective communication, time management, technological adeptness, and ethical conduct. Additionally, corporate culture significantly shapes secretaries' work attitudes and behaviors. To address challenges, secretaries adopt strategies like continuous learning and adaptability. This research highlights the importance of corporate culture, ethics, and ongoing skill enhancement in maintaining high standards of professionalism.